Acute Necrotizing Pancreatitis—Advances and Challenges in Management for Optimal Clinical Outcomes - Ioana Dumitrascu; Narcis Octavian Zarnescu; Eugenia Claudia Zarnescu; Mihai Radu Pahomeanu; Alexandru Constantinescu; Dana Galieta Minca; Radu Virgil Costea (Medicina)
Acute necrotizing pancreatitis (ANP), characterized by necrosis of pancreatic and/or peripancreatic tissues, is a potentially severe and life-threatening complication of acute pancreatitis, exhibiting a considerable mortality rate, particularly in the presence of infection, with rates ascending to 20–30%. Contrast-enhanced computed tomography is the definitive diagnostic standard, although treatment is determined by illness severity and the presence of secondary infection. The management of this condition has undergone considerable evolution, transitioning from initial surgical intervention to a more progressive, minimally invasive strategy. Initial management emphasizes aggressive fluid resuscitation, nutritional support, and monitoring of organ dysfunction. Infected necrosis is a critical factor influencing prognosis and requires intervention, typically starting with percutaneous drainage or endoscopic necrosectomy prior to evaluating surgical debridement. Recent advancements, such as the implementation of endoscopic and minimally invasive techniques, have enhanced outcomes by decreasing morbidity and mortality linked to open surgery. Despite these advancements, optimal treatment strategies are patient-specific and necessitate a multidisciplinary approach. Additional research is necessary to enhance guidelines and optimize patient outcomes.